Ray Rezeki NURSING CARE MANAGEMENT EXCELLENT SERVICE IN PATIENTS WITH CONGESTIVE HEART FAILURE (CHF) IN VIP WARD OF LATERSIA BINJAI HOSPITAL IN 2025 - silalahi, Ray Rezeki; Tahan Hasibuan; Sumiati; Fidea Poldryana Br Barus; Masda Yanti Lase; Elliska Sinaga, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Congestive Heart Failure (CHF) is a clinical syndrome characterized by the inability of the heart to pump blood effectively to meet the body's metabolic needs. Patients with CHF frequently experience shortness of breath, fatigue, edema, and decreased activity tolerance. Objective: To describe nursing care management in patients with CHF. Methods: This study used a descriptive case study design conducted in the VIP ward of Latersia Binjai Hospital. Data were obtained through interviews, physical examination, observation, and documentation studies. Results: The patient complained of shortness of breath during activity, weakness, edema in both lower extremities, and difficulty performing daily activities. The priority nursing diagnosis was decreased cardiac output related to altered cardiac rhythm. Nursing interventions included monitoring vital signs, assessing cardiac status, monitoring oxygen saturation, administering oxygen therapy, positioning in semi-Fowler position, and educating the patient regarding activity management. After 3 × 24 hours of nursing care, dyspnea decreased, oxygen saturation improved, and the patient appeared more comfortable. Conclusion: Nursing care management contributed to improving patient condition and reducing symptoms associated with CHF.